Ultra-steep spectrum emission in the merging galaxy cluster Abell 1914 - Mandal, S.; Intema, Huib; Shimwell, T.W.; Van Weeren, R.J.; Botteon, A.; Röttgering, H.J.A.; Hoang, D.N.; Brunetti, G.; De Gasperin, F.; Giacintucci, S.; Hoekstra, H.; Stroe, A.; et al. (EDP SCIENCES S A, 2019)
A number of radio observations have revealed the presence of large synchrotron-emitting sources associated with the intra-cluster medium. There is strong observational evidence that the emitting particles have been (re-)accelerated by shocks and turbulence generated during merger events. The particles that are accelerated are thought to have higher initial energies than those in the thermal pool but the origin of such mildly relativistic particles remains uncertain and needs to be further investigated. The galaxy cluster Abell 1914 is a massive galaxy cluster in which X-ray observations show clear evidence of merging activity. We carried out radio observations of this cluster with the LOw Frequency ARay (LOFAR) at 150 MHz and the Giant Metrewave Radio Telescope (GMRT) at 610 MHz. We also analysed Very Large Array (VLA) 1.4 GHz data, archival GMRT 325 MHz data, CFHT weak lensing data and Chandra observations. Our analysis shows that the ultra-steep spectrum source (4C38.39; α -2), previously thought to be part of a radio halo, is a distinct source with properties that are consistent with revived fossil plasma sources. Finally, we detect some diffuse emission to the west of the source 4C38.39 that could belong to a radio halo.